2009
DOI: 10.1159/000260060
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortins Mimic the Effects of Leptin to Restore Reproductive Function in Lean Hypogonadotropic Ewes

Abstract: Background/Aims: Leptin restores gonadotropic function in lean hypogonadotropic animals by an unknown mechanism. We aimed to test the hypothesis that restoration of gonadotropic function is a result of an upregulation of central acetylated melanocortin production. Methods and Results: Lean ovariectomised (OVX) ewes received intracerebroventricular (i.c.v.) infusions of leptin (or vehicle) for 3 days, which upregulated proopiomelanocortin (POMC) mRNA and restored pulsatile luteinizing hormone (LH) secretion. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 131 publications
3
31
0
Order By: Relevance
“…In this sense, we propose that GnIH may function as a molecular switch, between the two functions. This is consistent with the actions of a number of other peptides, which have opposing actions on reproduction and feeding, including NPY [40] and melanocortins [41], amongst others.…”
Section: Discussionsupporting
confidence: 82%
“…In this sense, we propose that GnIH may function as a molecular switch, between the two functions. This is consistent with the actions of a number of other peptides, which have opposing actions on reproduction and feeding, including NPY [40] and melanocortins [41], amongst others.…”
Section: Discussionsupporting
confidence: 82%
“…Investigations into the role of these peptides are confounded by the fact that most of these hormones and neuropeptides have both direct and indirect effects on the secretory function of the pituitary gland [4]. For example, recent studies have shown that leptin upregulates proopiomelanocortin gene expression and melanocortin production in the arcuate nucleus and Kiss1 messenger RNA (mRNA) levels in the preoptic area, leading indirectly to the restoration of LH secretion in lean ovariectomized ewes [26,27]. However, the identification of leptin receptor mRNA in 90% of gonadotrophs and 69% of somatotrophs in sheep is an indication of leptin activity and biological function in the pituitary gland [15], a phenomenon previously demonstrated by Zieba et al [11] and Amstalden et al [21] in bovine pituitary cells in vitro and postulated by McMahon et al [28] based on a study in calves.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the notion that adequate (or excessive) leptin levels are permissive of normal GnRH and/or LH secretion, whereas low leptin levels (in food-restricted, lean animals) signal energy deficiency. Leptin treatment of normal body weight OVX ewes reduces NPY gene expression, commensurate with reduction in food intake [128], but the same response is not seen in lean, foodrestricted OVX ewes [129], probably because there is were measured before treatment and at the end of treatment. Note that intracerebroventricular infusion of 4 mg/h leptin into food-restricted animals restored LH levels to normal in the food-restricted animals but had no effect in the animals on an ad lib diet.…”
Section: Metabolic Status and Reproductionmentioning
confidence: 99%